THE EFFECT OF LEVERAGE, PROFITABILITY AND PREVIOUS YEAR"™S AUDIT OPINION TOWARD GOING CONCERN AUDIT OPINION (STUDY CASE IN MANUFACTURING COMPANIES LISTED ON IDX) - wulandari, Fasha amalia (Jurnal KIAFE, 2021)
ABSTRACT This study aims to determine the effect of leverage, profitability and previous year"™s audit opinion on going concern audit opinion. The method used in this study is quantitative method, and the data is acquired from annual reports of companies listed on the Indonesian Stock Exchange (IDX). A total of 108 samples from 36 company and was taken through the purposive sampling method. The analysis technique used in this study is a logistic regression analysis. The result of this study indicates that leverage and previous year"™s audit opinion has no significant affect toward going concern audit opinion, profitability significantly affect going concern audit opinion.Keywords: Going Concern, Leverage, Profitability, and Previous Year"™s Audit Opinion.